Period of infectivity of animals challenged by Yersinia sp - Medeiros, Beatriz Maria Machado de; Shimizu, Mario Tsunezi; Falcão, Deise Pasetto (Revista de Saúde Pública, 1987)
Conventional swiss mice were innoculated intragastrically (IG) and intravenously (IV) with Yersinia enterocolitica serotypes 0:3, 0:8 and 0:9 and with Yersinia enterocolitica like strains. A control animal group was not innoculated. The period that strains remained in the cecal content after the IG and IV challenge was determined. After IG and IV innoculation, Yersinia enterocolitica serotypes 0:3, 0:8 and 0:9, considered adapted to man, were isolated from the cecal content for a longer period than those considered nonadapted.